Studi Kasus Kecelakaan Kerja pada Pekerja Pengeboran Migas Seismic Survey PT. X di Papua Barat - Winarto, Sigit; Denny, Hanifa Maher; Kurniawan, Bina (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2016)
ABSTRACTOil and gas industry is one of the industries with the level of risk of accidents is very high. Workplace accidents are generally caused by two main points, namely the behavior of unsafe working (unsafe act) and unsafe working conditions (unsafe conditions). The research objective is to analyze the actions and unsafe environment with workplace accidents in PT. X. This study was conducted analytic observational case control design. Number of samples 60 people, including 30 cases (Workers injured at work) and 30 controls (Workers who are not injured at work). Bivariate data analysis with chi square testand multivariat with test of regresi logistics. Factors related to accident of activity is period of activity (p value 0,006), worker action (p value 0,0001), and environment (p value 0,001), while factor which do not relate to accident of activityis age (p value 0,116), education (p value 1,000), training (p value 0,252), information (p value 1,000). By multivariat, environmental factor represent most having an effect on factor to accident of activity (p value 0,009; Exp.B 0,134). Action and environment have an effect on to occurence of accident of activity in PT X.Keywords: Action, environment, accident